PREVENTIONAL SCREENING: ALL PROS AND CONTRAS - Pogosova, N. V.; Yufereva, Yu. M.; Samorodskaya, I. V.; Boytsov, S. A. (Kardiovaskuli͡a︡rnai͡a︡ terapii͡a︡ i profilaktika, 2016)
Recently, medical community and mass media actively discuss the need for broad screening programs, criteria of those, investigation methods, frequency of start-up, etc. The article focuses on the main screening programs for adult citizens ofGreat Britain,USA,Australia,JapanandRussia.